POST-FIRE CONDITION AND RESTORATION OF FORESTS ON THE TERRITORY OF KOSTANAY REGION (Eurasian Journal of Ecology, 2024)
The results of field studies of post-fire condition and reforestation of Kostanay region are presented. The purpose of the research is to study and analyze the post-fire condition and forest regeneration in the territory of Kostanay region. It was established that the magnitude of post-fire tree declines and their radial growth in stands of the main forest-forming species are determined by the type and intensity of fire. Taking into account the types of forest landscapes using space images, we have identified 7 key and control (background) sites that characterize the disturbed and background undisturbed forest cover. Among them, the most affected by the forest fire are key areas №5 and №7, where a top fire of medium intensity occurred. The forest litter of these key areas was completely burned in a severe fire, the soil seed stock was destroyed, and low intensity of natural regeneration is expected. The average grade of all studied key sites is estimated by us as III and it is connected with untimely harvesting, which resulted in the reduction of annual growth of the plantation. Sanitary condition of plantations in key sites №1, №5, №7 is unsatisfactory in comparison with other sites. Soils of the investigated key sites are not compacted and favorable for growth. In key plot No.1 there was a compacted crust in the surface soil layer. Uneven natural regeneration of common pine after the fire is observed. Predominantly friendly seed sprouting is associated with more moistened lowlands and loosened soil areas. Factors impeding the natural renewal of pine forests include deep burning of the forest floor and soil cover, mechanical effects on the soil and seedlings of the equipment used to develop harems, the mushroom wavy rhizina (Rhizina undulata) which affects the roots of coniferous trees.Key words: forest, post-fire condition, forest restoration, key site, sanitary condition of trees, Kostanay region.